First Earth encyclopedia (DK First Reference, 2018)
Covering the essential curriculum areas of human geography, physical geography, geology, and ecology, First Earth Encyclopedia is a comprehensive introduction to the world around us. The engaging style of DK's First Reference series is applied to such topics as where and how people live, how to use maps, weather, world environments, and the changing climate- inspiring younger readers to think about their own place in the world. With superb artwork, straightforward text, buttons, and quizzes, First Earth Encyclopedia makes our world simple to understand. -- Provided by publisher.